Market acceptance of moving vehicle advertising in indonesia - Ramadhan Pangestu, Dimas; Dellyana, Dina (The Indonesian Journal of Business Administration, 2018)
Abstract. The advertising industry is growing rapidly nowadays, and many advertising companies are sticking to their advertising technology that has already been applied. However, the growing age of many companies engaged in industry innovation by offering to advertise with new and creative methods. VAS is present in 2017 in Indonesia as a start-up involved in advertising that provides a way of advertising by combining business models Facebook Ads with other running ads. The objective of this study was to find out how prepared the market would be to accept new VAS technologies, and whether the advertising methods offered by VAS would be more profitable for companies to advertise outside. The discussion of this problem will be analysed in several ways by examining internal and external, to know the internal of VAS using SW (Strength and Weakness), Business Model Canvas, and Technology Readiness Level. After knowing the internal-external then it will be analysed by using OT (Opportunities and Threat), PESTLE, Porter 5 Forces, Competitor Analysis, Standard and Market Acceptance, and this research will use AHP (Analytical Hierarchy Process). The results of this study show that the market has been able to accept new concepts to advertise with online and offline methods using outdoor media. The most important thing to be used as a reference to select advertising media is from the performance of the ad generated from the ad company. Keywords: Market Readiness, AHP, Advertising Industry, Business Mode, Advertising, Moving Vehicle Advertising Abstract. The advertising industry is growing rapidly nowadays, and many advertising companies are sticking to their advertising technology that has already been applied. However, the growing age of many companies engaged in industry innovation by offering to advertise with new and creative methods. VAS is present in 2017 in Indonesia as a start-up involved in advertising that provides a way of advertising by combining business models Facebook Ads with other running ads. The objective of this study was to find out how prepared the market would be to accept new VAS technologies, and whether the advertising methods offered by VAS would be more profitable for companies to advertise outside. The discussion of this problem will be analysed in several ways by examining internal and external, to know the internal of VAS using SW (Strength and Weakness), Business Model Canvas, and Technology Readiness Level. After knowing the internal-external then it will be analysed by using OT (Opportunities and Threat), PESTLE, Porter 5 Forces, Competitor Analysis, Standard and Market Acceptance, and this research will use AHP (Analytical Hierarchy Process). The results of this study show that the market has been able to accept new concepts to advertise with online and offline methods using outdoor media. The most important thing to be used as a reference to select advertising media is from the performance of the ad generated from the ad company. Keywords: Market Readiness, AHP, Advertising Industry, Business Mode, Advertising, Moving Vehicle Advertising